Unschooling vs. Classic Methods and Forms of Homeschooling from the Perspective of the Parents of Homeschooled Children - Rochovská, Ivana; Dolinská, Eva; Porubčanová , Dáša; Gažiová, Mária (Special Education, 2023)
The research is concerned with the possibilities of unschooling in Slovakia, the Czech Republic and Poland. It applies both quantitative and qualitative approaches. Using an open-ended questionnaire, it maps the opinions of 78 parents from Slovakia, the Czech Republic and Poland on the influence of the preferred methods and forms of homeschooling (unschooling, classical methods and forms) on the course and problems of the compulsory testing of a child in an umbrella school. Based on the research findings, it can be stated that the parents of homeschooled children perceive unschooling mainly as self-arranged education, the support of the child’s interests, and also complement it with other methods and forms of education. The problems during compulsory testing in an umbrella school, which were presented by the respondents, consisted firstly of subjectively negative evaluations of the course of the testing, statements concerning the respondents’ fear and descriptions of specific situations or the behaviour of the examiner. The research has also shown that the choice of the methods and forms of homeschooling does not affect whether the parents and children face more problems during the compulsory testing.
Keywords: homeschooling; unschooling; methods and forms of homeschooling; problems during the compulsory testing; classical methods and forms of homeschooling